Extreme winds at northern mid-latitudes since 1871 - S. Brönnimann; O. Martius; H. von Waldow; C. Welker; J. Luterbacher; G.P. Compo; P.D. Sardeshmukh; T. Usbeck (Meteorologische Zeitschrift, 2012)
Studying a sufficiently large sample of extremes or analysing the statistics of their occurrence, including trends, is hampered by the length of the existing observation-based record. New data sets such as the Twentieth Century Reanalysis (20CR), which consists of an ensemble of 56 members, significantly extend our record back in time. In this paper, we present examples of extremes of winds at northern hemisphere mid-latitudes in 20CR to illustrate challenges and opportunities for analysing extremes over a longer period than previously possible. For four representative storms from Europe and North America, 20CR provides a relatively good depiction of the synoptic-scale meteorological development, although it misses smaller scale features as well as local effects due to orography. For analysing trends of extreme winds, it is shown that the individual ensemble members should be used, rather than the ensemble mean, which appears to be biased towards lower wind speeds early in the record. For the studied locations, decadal variability and trends can best be characterised after around 1950, when the ensemble variance remains consistent. Different methodological approaches for studying changes in extreme winds are discussed. Finally, we show hemispheric maps of trends in extreme wind speeds since 1950.